The emerging role of oxylipins in thrombosis and diabetes - Tourdot, Benjamin E.; Ahmed, Intekhab; Holinstat, Michael (Frontiers in Pharmacology, 2014)
The prevalence of cardiovascular disease, the leading cause of death in the US, is predicted to increase due to the shift in age of the general population and increase in CVD risk factors such as obesity and diabetes. New therapies are required to decrease the prevalence of CVD risk factors (obesity and diabetes) as well as reduce atherothrombosis, the major cause of CVD related mortality. Oxylipins, bioactive metabolites derived from the oxygenation of PUFAs, play a role in the progression of CVD risk factors and thrombosis. Aspirin, a COX-1 inhibitor, decreases atherothrombotic associated mortality by 25%. These potent effects of aspirin have shown the utility of modulating oxylipin signaling pathways to decrease CVD mortality. The role of many oxylipins in the progression of CVD however is still uncertain or controversial. An increased understanding of the role oxylipins play in CVD risk factors and thrombosis could lead to new therapies to decrease the prevalence of CVD and its associated mortality.